Art : a visual history - Cumming, Robert, 1945- (DK, 2020)
Discover the history of Western art - from prehistory to the 21st century - through profiles of over 650 artists and their key works. Covering every era and over 650 artists, this comprehensive, illustrated guide offers an accessible yet expansive view of art history, featuring everything from iconic works and lesser-known gems to techniques and themes. Offering a comprehensive overview of Western artists, themes, paintings, techniques, and stories, Art- A Visual History is packed full of large, full-colour images of iconic works and lesser-known gems. Covering every era, from 30,000BCE to the present, it includes features on the major schools and movements, as well as close-up critical appraisals of 22 masterpieces - from Botticelli's Primavera to J. M. W. Turner's The Fighting Temeraire. With detailed referencing, crisp reproductions and a fresh design, Art- A Visual History is a must-have for anyone with an interest in art history - from first-time gallery goers to knowledgeable art enthusiasts. What makes great art? Discover the answer now! Art- A Visual History i's a must-have for anyone interested in the subject.